Contestations of resource extraction projects via digital media in two Nunavut communities - Scobie, Willow; Rodgers, Kathleen (Études/Inuit/Studies, 2013)
AbstractThis study examines the use of digital media in two Nunavut communities in response to proposed resource-extraction projects. Using Dahlberg’s (2011) concepts of counterpublics and deliberative democracy, the study links tactics employed in Baker Lake and Pond Inlet to broader activists’ use of digital media to reorganise social, political, and economic life. Drawing on the field of postcolonial studies, these cases demonstrate that social media are being incorporated into the development of new political imaginaries.